The nomenclature of two hybrid taxa in Carex sect. Vesicariae (Cyperaceae) currently assigned as Carex rostrata var. borealis and Carex stenolepis - Elven, Reidar; Pedersen, A. Tiril M.; Bjorå, Charlotte S. (Phytotaxa, 2017)
In a recent study of Carex sect. Vesicariae in northern Europe, two hybrid species were identified using microsatellite markers. Whereas both taxa already have names associated with them, we find that these names are not appropriate for use. In this study, the taxon previously described as C. rostrata var. borealis is raised to species level as the hybrid taxon Carex ×saamica (from C. rostrata × C. rotundata). We furthermore show that the name C. stenolepis, after designation of a lectotype, becomes a synonym of C. rostrata, and hence accept C. ×grahamii as the priority name for the hybrid taxon (from C. saxatilis × C. vesicaria) previously denoted as C. stenolepis. Arguments for these choices are given. Four other species names that have been assigned to the two hybrid taxa are discussed. Types are identified or designated for the names C. rostrata var. borealis, C. stenolepis, and C. ×grahamii. A key to the hybrid taxa and their parents is given.